A Qualitative Research On Worklife Based Problems Of Private School Teachers: The Case Of Elazig Province - Cerev, Gökçe; Çoşkun, Saliha (Fırat University, 2020)
Human capital is the most important resource that countries need for econo-mical, social and economic development. The main factor of the human capital resource is human, and as a result of the advancement in technology and production models, today, educated people have started to gain even more importance. Qualitative features of human capital are important as well as quantitative. Qualitatively increasing human capital to a higher level is provided by education. One of the most important actors of education is the teacher. With the changing world conditions and the principle of social state, the education service provided by the states with their own means is also provided by the private sector with the legal framework determined. With the education service offered in private education institutions, the working conditions of the teachers working in these institutions are regulated by different laws and regulations. In this study, the problems that teachers face in their business life who work in private schools are discussed. Target population of the study is composed of teachers working in private schools in Elazig province. In the study, a semi-structured interview form, which is one of the qualitative research methods, was used, and the problems of teachers were examined under five main headings: general problems, problems with management, problems with students, problems with parents and perceptions of professional expectations. Within the scope of field research in the study, 27 teachers were interviewed and content analysis was applied to the obtained data. As a result of the study It has been determined that teachers working in private schools have problems with management, parents and students, and wage and job security are sufficient.

Ülkelerin iktisadi, ekonomik, sosyal ve ekonomik kalkınması için ihtiyaç duy-duğu önemli kaynakların başında beşeri sermaye gelmektedir. Beşeri sermaye kaynağının temel unsuru insandır ve günümüzde gelişen teknoloji ile üretim modellerindeki ilerleme sonucu eğitimli insan daha da önem kazanmaya başlamıştır. Beşeri sermayenin nicel olduğu kadar nitel özellikleri de önemlidir. Beşeri ser-mayenin nitel olarak üst seviyeye çıkarılması eğitim ile olmaktadır. Eğitimin en önemli aktörlerinden birisi de öğretmendir. Değişen dünya şartları ile sosyal devlet ilkesi gereği devletlerin kendi imkânları ile yerine getirdiği eğitim hizmeti belirlenen yasal çerçeve ile özel sektör tarafından da yapılmaktadır. Özel eğitim kurumlarında sunulan eğitim hizmeti ile bu kurumlarda çalışan öğretmenlerin çalışma koşulları farklı yasa ve yönetmeliklerle düzenlenmiştir. Bu çalışmada özel okullarda çalışan öğretmenlerin çalışma hayatında karşılaş-tıkları sorunlar ele alınmıştır. Çalışmanın evrenini Elazığ ilinde bulunan özel okul öğretmenleri oluşturmaktadır. Çalışmada nitel araştırma yöntemlerinden yarı yapılandırılmış mülakat formu kullanılmış, öğretmenlerin sorunları genel sorunlar, yönetimle yaşadıkları sorunlar, öğrenci ile yaşadıkları sorunlar, veliler ile yaşa-dıkları sorunlar ve mesleki beklenti algıları olmak üzere beş ana başlıkta incelen-miştir. Çalışmada alan araştırması kapsamında 27 öğretmenle mülakat yapılmış elde edilen verilere içerik analizi uygulanmıştır. Çalışmanın sonucunda özel okul öğretmenlerinin yönetim, veli ve öğrencilerle sorunlar yaşadığı, ücret ve iş güven-cesinin yetersi olduğu tespit edilmiştir.
ÖZEL OKUL ÖĞRETMENLERİNİN ÇALIŞMA SORUNLARI ÜZERİNE NİTEL BİR ARAŞTIRMA: ELAZIĞ İLİ ÖRNEĞİ